Cytotoxicity and Survival Fitness of Invasive covS Mutant of Group A Streptococcus in Phagocytic Cells - Chiang-Ni, Chuan; Shi, Yong-An; Lai, Chih-Ho; Chiu, Cheng-Hsun (Frontiers in Microbiology, 2018)
Group A streptococci (GAS) with spontaneous mutations in the CovR/CovS regulatory system are more invasive and related to severe manifestations. GAS can replicate inside phagocytic cells; therefore, phagocytic cells could serve as the niche to select invasive covS mutants. Nonetheless, the encapsulated covS mutant is resistant to phagocytosis. The fate of intracellular covS mutant in phagocytic cells and whether the intracellular covS mutant contributes to invasive infections are unclear. In this study, capsule-deficient (cap-) strains were utilized to study how intracellular bacteria interacted with phagocytic cells. Results from the competitive infection model showed that the cap- covS mutant had better survival fitness than the cap- wild-type strain in the PMA-activated U937 cells. In addition, the cap- covS mutant caused more cell damages than the cap- wild-type strain and encapsulated covS mutant. Furthermore, treatments with infected cells with clindamycin to inhibit the intracellular bacteria growth was more effective to reduce bacterial toxicity than utilized penicillin to kill the extracellular bacteria. These results not only suggest that the covS mutant could be selected from the intracellular niche of phagocytic cells but also indicating that inactivating or killing intracellular GAS may be critical to prevent invasive infection.